Reduction of sawtooth amplitude by resonant magnetic perturbation. (22nd September 2020) - Li, Jianchao; Ding, Yonghua; Yu, Qingquan; Wang, Nengchao; Li, Da; Zhang, Xiaoqing; Han, Dongliang; Chen, Zhipeng; Yang, Zhoujun; Zhou, Song; Yan, Wei; Liang, Yunfeng; et al.
Abstract: Sawtooth crashes of large amplitude are detrimental to tokamak plasma confinement, and the amplitude has to be reduced for a fusion reactor. A novel method, i.e. applying m / n = 2/2 resonant magnetic perturbations (RMPs), is found to be able to reduce the sawtooth magnitude in J-TEXT tokamak experiments. The penetration of RMPs and formation of 2/2 locked island are found to be related to the reduction of sawtooth magnitude. With the available 2/2 RMP field, the sawtooth mitigation is reproducibly achieved with q a < 2.8 and n e < 2 × 10 19 m −3 in J-TEXT.